An empirical analysis of ASEAN's labor-intensive exports - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2009)
This paper investigates the factors affecting the demand for the Association of Southeast Asian Nations' (ASEAN) labor-intensive exports. Results obtained using a panel data set including exports to 25 countries indicate that an appreciation in ASEAN countries would substantially reduce exports of clothing, furniture, and footwear. In addition, an increase in foreign income and an appreciation among competitors would raise ASEAN's exports. These results indicate that profit margins for labor-intensive manufactures are thin and that slow growth abroad will curtail ASEAN's exports. These findings imply that policymakers should seek to promote domestic demand, expand the technological base, and consider exchange rate coordination to mitigate beggar-thy-neighbor policies.
Keywords: F32; F41; 330